1998
DOI: 10.1023/a:1008438109725
|View full text |Cite
|
Sign up to set email alerts
|

UGT1A1 genotypes and glucuronidation of SN-38, the active metabolite of irinotecan

Abstract: These results support the idea that the patient with 7/7 genotype has an impaired capacity for glucuronidation of SN-38.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
105
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(108 citation statements)
references
References 6 publications
1
105
1
1
Order By: Relevance
“…In fact, Hosokawa et al 21) reported inter-individual variability of CCE activity in liver. Although our hypothesis was not supported by this study, other mechanisms such as hepatobiliary secretion, which has already been shown to have inter-individual variability, 11,12) might have interfered in some way. Although conversion from irinotecan to SN-38 is evident in liver, 1,13,14,17,18) small intestine, 13) colon, 14) plasma 15) and tumor tissue, 14,16) their mutual correlations have not been reported.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In fact, Hosokawa et al 21) reported inter-individual variability of CCE activity in liver. Although our hypothesis was not supported by this study, other mechanisms such as hepatobiliary secretion, which has already been shown to have inter-individual variability, 11,12) might have interfered in some way. Although conversion from irinotecan to SN-38 is evident in liver, 1,13,14,17,18) small intestine, 13) colon, 14) plasma 15) and tumor tissue, 14,16) their mutual correlations have not been reported.…”
Section: Discussioncontrasting
confidence: 82%
“…4) Therefore, predicting its toxicity in any given patient has been difficult in contrast to other agents such as carboplatin, for which a sophisticated method for individualizing dosing is available. 10) As one of the mechanisms underlying this inter-individual variability of irinotecan metabolism, Ando et al 11,12) demonstrated that bilirubin UDP-glucuronosyltransferase 1 gene promoters with excessive TATAA elements were responsible for reduced conjugation of SN-38 to SN-38-glucuronide (SN-38G), resulting in a reduction of SN-38 detoxication in the liver. However, it is still unresolved whether this mechanism alone explains the entire inter-individual variability of the toxicity and pharmacokinetics of this drug.…”
mentioning
confidence: 99%
“…9 In addition, UGT1A1*28 has been identified as a risk factor for unwanted drug side effects exemplified by the possibility of severe toxicity of the anti-cancer drug irinotecan. [10][11][12][13] Gilbert's disease can therefore be regarded as a sentinal phenotype pointing to a pharmacogenetic risk constellation of UGT1A1*28-carrying individuals. 13 UGT1A1 is a member of the UGT1A family of transferases encoded on human chromosome 2.…”
mentioning
confidence: 99%
“…The variable number of TA repeats ranges from five to eight copies, six TA repeats represent the most common allele, with up to 33% in Caucasians having a variant allele containing seven repeats (UGT1A1*28) (Iyer et al, 1999). Significant associations between patients with the UGT1A1*28 allele and reduced UGT1A1 expression, and, consequently, reduced SN38 glucuronidation have been shown in several studies (Ando et al, 1998;Iyer et al, 1999;Iyer et al, 2002). Assessment of the presence of the UGT1A1*28 allele in patients prior to irinotecan treatment may predict individuals at risk for severe toxicity from irinotecan, allowing the selection of lower doses or alternative therapies.…”
Section: Udp-glucuronosyltransferase 1a1 (Ugt1a1)mentioning
confidence: 99%